1981
DOI: 10.1007/bf00848401
|View full text |Cite
|
Sign up to set email alerts
|

Use of lectins as probes for analyzing embryonic induction

Abstract: Lectins were used as probes to investigate the mechanism of embryonic induction. Concanavalin (Con A) and gorse agglutinin out of 7 species of lectins tested were found to have strong neural-inducing effect on the presumptive ectoderm of newt gastrulae. Their effects were abolished by the addition of α-methyl-D-mannoside and α-L-fucose, respectively. Succinyl-Con A had a weak inducing activity in comparison to Con A. Autoradiography ofH-Con A-treated explants revealed that Con A bound to the inner surface, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0
2

Year Published

1982
1982
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 26 publications
2
11
0
2
Order By: Relevance
“…We found that the upregulation of a FOS-related protein, determined immunochemically, can be induced in animal cap explants of early gastrula (stage 8a) of the amphibian Pleurodeles waltl by noggin as well as by the lectin Con A, which also has neuralizing properties (Takata et al 1981;Gualandris et al 1985 (Murphy et al 1991). In the pheochromocytoma cell line PC12, the mechanism by which L-type voltage-sensitive calcium channels regulate c-fos transcription has been extensively studied (Morgan & Curran 1986; Piechaczyk & Blanchard 1994).…”
Section: Discussionmentioning
confidence: 87%
“…We found that the upregulation of a FOS-related protein, determined immunochemically, can be induced in animal cap explants of early gastrula (stage 8a) of the amphibian Pleurodeles waltl by noggin as well as by the lectin Con A, which also has neuralizing properties (Takata et al 1981;Gualandris et al 1985 (Murphy et al 1991). In the pheochromocytoma cell line PC12, the mechanism by which L-type voltage-sensitive calcium channels regulate c-fos transcription has been extensively studied (Morgan & Curran 1986; Piechaczyk & Blanchard 1994).…”
Section: Discussionmentioning
confidence: 87%
“…This may be explained by the fact that the oligosaccharide has a higher association constant with Con A than the simple sugar methyl-a-D-mannoside (1 8). It is interesting to note that neural induction by Con A was greatly inhibited by methyl-a-D-mannoside even at 1 mM concentration (30).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Con A can induce the competent ectoderm to form archencephalic neural tissues (8,10,17,30). The mode of action of Con A seems very similar to that of the living organizer factor (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations